2015
DOI: 10.1016/j.ejvs.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative Cone Beam Computed Tomography can Help Avoid Reinterventions and Reduce CT Follow up after Infrarenal EVAR

Abstract: CA is better than CBCT in detecting and categorizing endoleaks but CBCT (with or without contrast) is better than CA for detection of kinks or stentgraft compression. CTA plus CBCT identified all significant complications noted on the 1 month follow up CTA. The use of intra-operative CA and CBCT could replace early CTA after standard EVAR thus reducing overall radiation and contrast use. Technical development might further improve the resolution and usefulness of CBCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 18 publications
1
42
0
2
Order By: Relevance
“…Our report also illustrates the utility of performing immediate assessment with CBCT, which was not done at the time of the initial implant. Intraoperative assessment with CBCT ensures immediate identification of stent kink, compression or infolding, and endoleaks and may decrease the rate of avoidable reinterventions as illustrated by this case 11, 12…”
Section: Discussionmentioning
confidence: 96%
“…Our report also illustrates the utility of performing immediate assessment with CBCT, which was not done at the time of the initial implant. Intraoperative assessment with CBCT ensures immediate identification of stent kink, compression or infolding, and endoleaks and may decrease the rate of avoidable reinterventions as illustrated by this case 11, 12…”
Section: Discussionmentioning
confidence: 96%
“…This resulted in a significant reduction in both radiation exposure and contrast volume [74]. Another group found that cone beam CT was better able to identify stent-graft compressions and kinks than digital subtraction contrast angiography, but did miss (type II) endoleaks that were detected on digital subtraction angiography (of note, none of the "missed" endoleaks required further intervention) [75]. This combination of completion imaging may obviate the need for early follow-up CTA.…”
Section: Follow-up Imagingmentioning
confidence: 92%
“…With the progressive development of hybrid operating rooms in vascular surgery, cone-beam CT (CBCT) mounted on a C-arm becomes an increasingly commonly used imaging technology in vascular interventions, such as endovascular aneurysm repair (EVAR), thanks to its capability of 3D imaging of arterial structures and less radiation in comparison with multi-slice CT [1–5]. There are at least two advantages of 3D CBCT acquisition during EVAR.…”
Section: Introductionmentioning
confidence: 99%